Does history matter? / making and debating citizenship. ommigration and refugee policy in Australia and New Zealand - Wanna, John; Tavan, Gwenda (ANU E Press, 2009)
Kolektivní monografie se zaměřuje na problematiku občanství, uprchlictví a imigrační politiky v Austrálii a na Novém Zélandu.